2021
DOI: 10.1101/2021.06.08.21258546
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inequalities in healthcare disruptions during the Covid-19 pandemic: Evidence from 12 UK population-based longitudinal studies

Abstract: Background: Health systems worldwide have faced major disruptions due to COVID-19 which could exacerbate health inequalities. The UK National Health Service (NHS) provides free healthcare and prioritises equity of delivery, but the pandemic may be hindering the achievement of these goals. We investigated associations between multiple social characteristics (sex, age, occupational social class, education and ethnicity) and self-reported healthcare disruptions in over 65,000 participants across twelve UK longitu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…Substantial reductions in primary care consultations were observed across the UK during the first wave of the COVID-19 pandemic, 14 , 15 with people from minority ethnic groups reporting greater healthcare disruption than individuals from White ethnic groups. 16 However, the difference in primary care utilisation between migrants and non-migrants in England and how the pandemic has affected this, including the important interplay between migration and ethnicity within increasingly diverse communities, has not been studied. This is needed to help identify inequalities, and to inform service provision and policy.…”
Section: Introductionmentioning
confidence: 99%
“…Substantial reductions in primary care consultations were observed across the UK during the first wave of the COVID-19 pandemic, 14 , 15 with people from minority ethnic groups reporting greater healthcare disruption than individuals from White ethnic groups. 16 However, the difference in primary care utilisation between migrants and non-migrants in England and how the pandemic has affected this, including the important interplay between migration and ethnicity within increasingly diverse communities, has not been studied. This is needed to help identify inequalities, and to inform service provision and policy.…”
Section: Introductionmentioning
confidence: 99%
“…Higher pre-pandemic psychological distress was associated with increased odds of healthcare disruption, loss of employment and income, and reduced working hours or being furloughed, but it was not associated with housing disruption during the pandemic 38 . Another pre-print using data from over 65,000 individuals in 12 longitudinal studies, including CovidLife, found that healthcare disruption during COVID-19 was greater in female participants, older people, ethnic minorities, and those from more disadvantaged social classes 39 .…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“… 1 2 However, young people have experienced considerable indirect effects of the pandemic through disruptions to health and other services, including much greater relative decreases in planned hospital admissions than adults. 3 Among adults, disruptions to healthcare during the pandemic have not been borne equally, 4 5 and it is likely that certain groups of young people have also been disproportionately affected.…”
Section: Introductionmentioning
confidence: 99%